A literary work as self-reflection of the author: Why and how it is manifested - Idha Nurhamidah; Sugeng Purwanto; Nur Ekaningsih (EduLite: Journal of English Education, Literature and Culture, 2019)
Anyone on earth may at one time or another reflects him or herself in a way he or she feels comfortable—be it as simple as writing up a phrase “Go to Hell with Communism!” on a wall of an old building. In this respect, he or she has reflected him or herself that he or she does not agree with the ideology of communism. The current study investigated to justify that literary works reflect the ‘selves’ of the authors in one or more possible ways. A poet may, to reflect him or herself, be characterized as employing particular styles or diction. A novelist may try to involve in one of the characters he or she has developed in order to reflect him or herself. In this study, a novel entitled “Pride and Prejudice” by Jane Austen (1813) was investigated to justify that the author (Austen) reflected herself in one of the characters in the novel. The findings reveal that Austen tried to manifest herself in one of the characters called ‘Elizabeth Bennet’ in three different ways: (1) how she behaved in her family (loving all family members, especially being close to her father), (2) how she spent most of the time—reading to broaden the horizon of thinking. As a result, she could (3) skillfully negotiate with other people through their positive sides. The study concludes that everyone, of whatever professions he or she has, will reflect him or herself in a way he or she may not realize.